Fungistatic and Fungicidal Capacity of a Biosurfactant Extract Obtained from Corn Steep Water - Alejandro López-Prieto; Xanel Vecino; Lorena Rodríguez-López; Ana Belén Moldes; José Manuel Cruz (Foods, 2020)
Biosurfactants are surface-active compounds that are produced by microorganisms, which in addition to their surfactant capacity, can possess interesting antimicrobial activities that are used in their incorporation into the agrifood industry. In this work, the preservative capacity of a novel biosurfactant extract obtained from a residual stream of the corn-milling industry was evaluated against two different fungi (Aspergillus brasiliensis and Candida albicans) under different biosurfactant concentrations (0.33–0.99 mg/mL), temperatures (4–40 °C), and incubation times (5–11 days). All the assays started with the same concentration of fungi (2 × 106 CFU/mL). The results showed that temperature played an important role in the fungicidal and fungistatic effects of this biosurfactant extract. It was observed that at a low biosurfactant concentration (0.33 mg/mL) and at low temperatures in the range tested, this biosurfactant extract possessed an important fungicidal effect (complete inhibition) on A. brasiliensis, while at intermediate temperatures, it achieved a fungistatic effect (50% of inhibition) at the highest concentration. Regarding C. albicans, it was observed that this strain was more resistant than A. brasiliens, although it was possible to achieve growth inhibitions of 76.3% at temperatures of 40 °C after 8 days of incubation with a biosurfactant concentration of 0.99 mg/mL. This work supports the possible application of biosurfactants extracted from corn steep water as preservatives and antimicrobial agents against fungal contaminations on agrifood products.